THE RELATIONSHIP OF FAMILY SOCIOECONOMIC STATUS AND DIET COMPLIANCE WITH HYPERTENSION IN THE ELDERLY - Duby Nur Komara; Dewi Dolifah; Amanda Puspanditaning Sejati (Buletin Veteriner Udayana, 2024)
Low socioeconomic status is a potential factor for the occurrence of hypertension. Low socioeconomic status is associated with poorer health status, this is related to lifestyle and diet quality that is low or less healthy. The key to following a hypertension diet is compliance, the extent to which a person follows or adheres to dietary rules and recommendations to control hypertension. This study aims to analyze the relationship between family socioeconomic status and hypertension diet compliance among the elderly in Licin Village. This research used quantitative correlation through a cross-sectional approach with data collection techniques using instruments in questionnaires and then analyzed using the Chi-square test. The research sample consisted of 71 people using a simple random sampling technique determined using the Slovin formula. The research results showed that 48 people (67.6%) had moderate socioeconomic status, and 53 people (74.6%) had a non-compliant diet level. From the results of statistical tests, it was found that there was a significant relationship between p-value < α value (0.000 < 0.05) of family socio-economic status with hypertension diet compliance in the elderly in Licin Village, with a correlation coefficient value (P=0.027). It can be concluded that there is a significant relationship between family socioeconomic status and hypertension diet compliance in the elderly. It is hoped that Cimalaka Health Center health workers will increase their regular examinations, especially in detecting high blood pressure for hypertension sufferers, and increase the provision of information or health promotion to families, especially hypertension sufferers.